Association Between Adjuvant Sorafenib and the Prognosis of Patients With Hepatocellular Carcinoma at a High Risk of Recurrence After Radical Resection - Li, Qingli; Song, Tianqiang (Frontiers in Oncology, 2021)
Background: The use of sorafenib in the adjuvant management of hepatocellular carcinoma (HCC) is controversial. Aim: To analyze the effect of adjuvant sorafenib therapy in patients with HCC patients at high recurrence risk after radical resection. Methods: This was a retrospective study of patients who underwent radical resection (R0 resection) for HCC at the Cancer Hospital of Tianjin Medical University from August 2009 to August 2017. All patients had microvascular invasion and were evaluated for portal vein tumor thrombus. The outcomes were overall survival (OS), recurrence-free survival (RFS), and survival after recurrence. Propensity score matching (PSM) was used. Results: Before matching, there were 56 and 167 patients in the sorafenib and non-sorafenib groups. After PSM, there were 42 patients/group, and there were no significant differences in patient characteristics (all P>0.05). After PSM, compared with the non-sorafenib group, the sorafenib groups showed longer median OS (34 vs. 26 months, P=0.032) and survival after recurrence (16 vs. 9 months, P=0.002), but no difference in RFS (14 vs. 11 months, P=0.564). Adjuvant sorafenib was the only factor independently associated with OS (HR=0.619, 95% CI: 0377-0.994, P=0.047). No factor was independently associated with RFS (all P>0.05). Conclusion: Although adjuvant sorafenib therapy for patients with HCC and high recurrence risk cannot reduce the recurrence risk of HCC, it is associated with longer survival time and lower risk of death.